Ethical and regulatory dimensions of the technological development process of a portable medical device for diabetic foot treatment : from bench to scale manufacturing - Nogueira, Vladimir França (2024)
The development of new technologies applied to health is inherently complex. Consequently, academia, government, society, and industry have been striving to accelerate the transition from basic research to the availability of new products for the population. The Brazilian regulatory system for medical devices encompasses ethical, technical, regulatory, economic, and social considerations to ensure safety and minimum technical standards for effectively addressing the proposed solution in accordance with its intended use. In this context, Translational Health Research (THR) emerges as a field aimed at promoting, among other elements, a set of actions and activities to transfer findings from basic research to the approval of technology, making it available to users/patients. This is achieved through translational stages that underpin Brazilian regulatory processes. Objective: To develop the THR process within the ecosystem of research, development, and innovation at a Public University in Brazil, as well as within the ethical and regulatory environment associated with the development of new medical products for the Brazilian healthcare system, using the Rapha® device as a case study. Methodology: This study employed a structured approach to investigate the technological development process for medical devices, focusing on the Rapha® device. Initially, data were collected on the R&D&I ecosystem in public universities, identifying conditions for the social integration of technologies. Next, the translational research process was characterized, covering stages, markers, involved entities, and ethical and regulatory aspects, based on the Rapha® case study. Finally, the technological maturity and market potential of the device were evaluated using tools such as the SWOT matrix, Technology Readiness Levels (TRL), and Medical Device Readiness Levels (MDRL), ensuring an integrated analysis of the development and application of the device within the public healthcare system. Results: The transformation of knowledge generated at the University of Brasília into applied innovation resulted in the development of the Rapha® device, a product with potential for integration into healthcare services. This process led to patents and technology transfers, reinforcing their link to innovation. It was observed that THR operates as a non-linear process, as evidenced in the Rapha® case study. Among the challenges encountered were the "valleys of death," particularly during the regulatory and production transitions between the T3 and T4 phases, which are critical for making the technology available to the Brazilian market. The translational stages T0, T1, T2, and T3 were identified and complemented by an evaluation of the technological maturity levels using TRL and MDRL, as well as a strategic analysis with the SWOT matrix. Conclusion: The translation of knowledge generated by the university, represented by the Rapha® device, proved to be a successful case of applied research with the potential for a positive impact on Brazilian public health and the economy. Identifying the paths followed by the Research, Development, and Innovation (R&D&I) of this technology and its respective technological maturity levels reveals a replicable strategy for other academic innovations, highlighting the importance of a collaborative ecosystem for the development of technologies that benefit the population.